Atores hegemônicos e não hegemônicos: territorialidades históricas do Município Carambeí – PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The present dissertation tries to understand the formation and entanglements that occurred from the first inhabitants of the old colony Carambeí, until the present moment. Giving visibility to different voices of the ethnic groups that together configure the municipality, of which it embraces an ethnic miscegenation and hierarchical social structures linked to a culture of representation. The purpose of this work is to characterize the foundation of a discourse and the formation of the municipality through hegemonic and non-hegemonic actors. It supports the reconfiguration of a critical tradition that has been present for decades. The methodology used is oral history, which provides visibility to an overshadowed part of the Carambeí root. Divided into three chapters, the first through orality of the residents and concomitant field-city relationship. The second chapter clarifies and dialogues with the interviews (oral history) and documented history, emphasizing the different voices. The third chapter presents analyzes using interviews initially transcribed in a database, and later in graphs that help and better give visibility to the study. Thus, the work establishes a link between the empirical (residents of the municipality), with the scientific production, with conceptual discussions about territory, oral history, field-city relationship and memory.
Keywords: Carambeí; Território; História Oral; Atores hegemônicos e não hegemônicos; Carambeí; Territory; Oral history; Hegemonic actors and non-hegemonic; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA